Penerimaan Diri Siswa dengan Pengalaman Perceraian Orang Tua di SMP Negeri 1 Sinjunjung - Syahril, Putri Wie; Febriani, Rahmi Dwi; Syukur, Yarmis; Nurfarhanah, Nurfarhanah; Arafani, Adnan (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
Parental divorce is a critical life event that can significantly affect a child’s psychological development, particularly in terms of self-acceptance. This study aims to describe the level of self-acceptance among junior high school students who have experienced parental divorce, examined by the length of time since the divorce. Using a quantitative descriptive approach, the research involved 35 students of SMP Negeri 1 Sijunjung selected through total sampling. Data were collected using a self-acceptance scale adapted from previous studies and analyzed with descriptive statistics via JASP. Results indicate that most students demonstrate high (65.7%) or very high (8.6%) levels of self-acceptance, with a tendency for higher acceptance over longer periods since parental divorce. These findings highlight the role of consistent psychosocial support, cultural factors, and school-based counseling in fostering resilience and healthy self-acceptance in adolescents from divorced families.